simplify ( y^2 – 7y+4) ( 3y^2 -2) + ( y-1) ( y^2- 2y) ​

Question

simplify ( y^2 – 7y+4) ( 3y^2 -2) + ( y-1) ( y^2- 2y) ​

in progress 0
Liliana 2 months 2021-08-12T06:29:09+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-12T06:30:35+00:00

    Given :–

    • An equation, (y² – 7y + 4)(3y² – 2) + (y – 1)(y² – 2y)

    To Find :–

    • Simplify the given equation.

    Solution :–

    The given equation is,

    ⟹ (y² – 7y + 4)(3y² – 2) + (y – 1)(y² – 2y)

    Open the both small brackets.

    ⟹ [3y⁴ – 21y³ + 10y² – 14y – 8] + [y³ – y² – 2y² – 2y]

    Now, open the both big brackets,

    ⟹ 3y⁴ – 21y³ + 10y² – 14y – 8 + y³ – y² – 2y² – 2y

    Arrange the same variable numbers,

    ⟹ 3y⁴ – 21y³ + y³ + 10y² – 3y² – 14y – 2y – 8

    Now, solve this.

    We obtain,

    ⟹ 3y⁴ – 20y³ + 7y² – 16y – 8

    Hence,

    The simplified equation of the given equation (y² – 7y + 4)(3y² – 2) + (y – 1)(y² – 2y) is 3y⁴ – 20y³ + 7y² – 16y – 8.

    0
    2021-08-12T06:30:38+00:00

    Answer:

     \huge\text {heya}

    Answer to your question:

    →(y²-7y+4)(3y²-2y)+(y²+1)(y²+2y)

    =>3y⁴-2y²-21y³+14y+12y²-8+y³+2y²+y²+2y

    =>3y⁴+13y²-20y³+16y-8

    So, this is the answer

    Hope helped!!

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )